Vigenere Cipher Cryptography for Secure Data Transmission in IoT Smart Door Using QR Code - Riski Arasyid; Syamsul Bahri; Kasliono (Jurnal Media Informasi Teknologi, 2026)
The Smart Door system based on the Internet of Things (IoT) using QR Code offers automated access but remains vulnerable to data sniffing attacks. This study implements the Vigenère Cipher algorithm to encrypt transmitted data and analyzes the ciphertext's resistance to attacks as well as its impact on communication delay. The system is built using ESP32-CAM as the QR scanner and NodeMCU ESP32 as the main controller, with encryption applied across three communication paths: ESP32-CAM to server, server to database, and server to ESP32. Testing involved data sniffing, delay analysis, and ciphertext evaluation using tools such as dCode and CryptoTool. From 20 sniffed QR Code results, 10 random samples were tested, and only 3 were recognized as Vigenère Cipher and none were decrypted successfully. In the server-to-ESP32 path, only 1 out of 10 ciphertexts was detected and all remained undeciphered. The average delay was recorded at 2.473 seconds (door unlocking) and 3.491 seconds (buzzer activation), with variations due to network stability. The results indicate that Vigenère Cipher effectively enhances data security in resource-constrained IoT devices, although delay optimization is needed to meet real-time system requirements.